System-Based Reliability Analysis Of The Preventive Maintenance Strategies Of A Reinforced Concrete Bridge - Ocholi, A.; Nyihemba, L.D.; Ejehl, S.P.; Abubakar, I. (Ife Journal of Technology, 2019)
system-based time-dependent reliability analysis was carried out over the service life of a reinforced concrete bridge using a MATLAB program, BRELA (BRidge RELiability Analysis). Component reliability analysis for the bridge members was evaluated using a built-in MATLAB based sub program in BRELA and the system reliability index “βsys” calculated over time using the system reliability analysis component of the main program. The bridge was modelled as a hybrid/combined system (series-parallel subsystems). Nineteen (19) failure modes for the bridge components were identified and their limit state functions incorporating load growth and deterioration models of the steel reinforcement due to corrosion were developed. The result of the system reliability analysis shows a system performance loss of 25.65–100% as corrosion rate increased from 0–0.06 mm/year for a load growth rate of 0.5%. Considering several realistic preventive maintenance options and their associated costs, the reinforced concrete bridge is maintained by ensuring that the commencement of preventive maintenance measures is a function of the deterioration rate and the target performance level. For a target system reliability index of 3.0 with a load growth of 0.5%, preventive measures have to be implemented around 30, 25 and 20 years after construction for corrosion rates of 0.02, 0.04 and 0.06 mm/year respectively.